2018
DOI: 10.1037/cpb0000118
|View full text |Cite
|
Sign up to set email alerts
|

Towards a process-based typology of workplace coaching: An empirical investigation.

Abstract: Research into work-based coaching has been led by the need of a new discipline to demonstrate effectiveness of this practice, often assuming that coaching is a homogeneous activity. A multifaceted and multi-purposeful nature of coaching now requires development of meaningful typologies that reflect this diversity and grounded in the analysis of coaching process. There are many reasons empirical investigations of the coaching process are extremely rare. The aim of this article is to present such a study leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 58 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…On reviewing their own sessions with the help of a Q-sort procedure, coachees focused mainly on their interpersonal needs and on the space and structure to develop new perspectives, whereas coaches focused more on the application of their expertise and on choices made during their interventions. Factor analysis showed that all Q sorts spanned only two factors: client-led coaching and process-led (directive) coaching (Myers & Bachkirova, 2018). Two sessions could be shown to be more client-centered and two more directive (with the other two in between).…”
Section: Results: An Overview Of Research Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…On reviewing their own sessions with the help of a Q-sort procedure, coachees focused mainly on their interpersonal needs and on the space and structure to develop new perspectives, whereas coaches focused more on the application of their expertise and on choices made during their interventions. Factor analysis showed that all Q sorts spanned only two factors: client-led coaching and process-led (directive) coaching (Myers & Bachkirova, 2018). Two sessions could be shown to be more client-centered and two more directive (with the other two in between).…”
Section: Results: An Overview Of Research Findingsmentioning
confidence: 99%
“…In all these apparently important ingredients of coaching, the eye of the beholder matters a great deal: Coachees, coaches, and observers look very differently at their common endeavor (see, e.g., de Haan & Nieß, 2015; Myers & Bachkirova, 2018; Will et al, 2016). When studying important aspects such as the coaching relationship, trust, and the coach’s empathy, it is important therefore to specify the perspective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important consideration for future research is the collection of multiple sources of data among key stakeholders in the coachee's environment (e.g., coach, line manager, subordinates, peers, human resource development personnel) to overcome or reduce the risk of bias associated with self‐reported ratings. This recommendation becomes highly important as qualitative studies (e.g., De Haan, 2019; Lai & Smith, 2021; Myers & Bachkirova, 2018) demonstrate how the multi‐purpose and multifaceted nature of coaching is reflected in varied agendas and objectives among coaching stakeholders in the three‐way joint coaching alliance (i.e. coach, coachee, sponsor organization).…”
mentioning
confidence: 99%